Separably real closed local rings (1985)
It is well known that several types of "variable reals" arising in topos theory (Dedekind reals,  Cauchy reals, smooth reals, etc.) are not real closed,  in the sense that a polynomial (with "variable real" coefficients) may sign in an interval without having a zero in that interval.